2017
DOI: 10.1021/jacs.7b02213
|View full text |Cite
|
Sign up to set email alerts
|

The New Chemical Reporter 6-Alkynyl-6-deoxy-GlcNAc Reveals O-GlcNAc Modification of the Apoptotic Caspases That Can Block the Cleavage/Activation of Caspase-8

Abstract: O-GlcNAc modification (O-GlcNAcylation) is required for survival in mammalian cells. Genetic and biochemical experiments have found that increased modification inhibits apoptosis in tissues and cell culture and that lowering O-GlcNAcylation induces cell death. However, the molecular mechanisms by which O-GlcNAcylation might inhibit apoptosis are still being elucidated. Here, we first synthesize a new metabolic chemical reporter, 6-Alkynyl-6-deoxy-GlcNAc (6AlkGlcNAc), for the identification of O-GlcNAc-modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 54 publications
(93 reference statements)
1
57
0
Order By: Relevance
“…We next investigated the downstream targets of O-GlcNAcylation. A previous study found that the cleavage of apoptotic caspases could be blocked by O-GlcNAcylation 23 . In our study, the major intrinsic apoptotic caspases, namely caspase-3 and 9, were also O-GlcNAcylated in the parental and resistant cells.…”
Section: Resultsmentioning
confidence: 97%
“…We next investigated the downstream targets of O-GlcNAcylation. A previous study found that the cleavage of apoptotic caspases could be blocked by O-GlcNAcylation 23 . In our study, the major intrinsic apoptotic caspases, namely caspase-3 and 9, were also O-GlcNAcylated in the parental and resistant cells.…”
Section: Resultsmentioning
confidence: 97%
“…1 a, b). This result is strengthened by two recent works which have identified MCM2, MCM3, MCM4 and MCM5 as O -GlcNAc-modified proteins using metabolic incorporation of chemical GlcNAc analogue probes combined with click chemistry labelling [ 76 , 77 ]. Using a mass-tagging strategy, we show that the O -GlcNAcylated MCM proteins are of low stoichiometry (from less than 3% for MCM2 and MCM4, to 13% for MCM6) (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…For example, we have demonstrated that subtle changes in the MCR structure can make them preferential substrates for OGT. This approach has led to the development of multiple more‐selective O‐GlcNAc MCRs including Ac 4 GlcNAlk, Ac 3 6AzGlcNAc, Ac 3 6AlkGlcNAc, and Ac 4 2AzGlc (Chuh et al., 2017; 2014; Zaro et al., 2017; Zaro et al., 2011). Second, treatment of cells with MCRs may cause increased flux into the corresponding donor sugar, resulting in higher than typical amounts of protein modification.…”
Section: Commentarymentioning
confidence: 99%
“…Several different MCRs have been developed for the investigation of O‐GlcNAcylated proteins (Fig. 1) (Boyce et al., 2011; Chuh et al., 2017; Chuh, Zaro, Piller, Piller, & Pratt, 2014; Hang, Yu, Kato, & Bertozzi, 2003; Hao et al., 2019; Li et al., 2016; Vocadlo, Hang, Kim, Hanover, & Bertozzi, 2003; Zaro, Batt, Chuh, Navarro, & Pratt, 2017; Zaro, Yang, Hang, & Pratt, 2011). Basic Protocol 1 describes a basic procedure for incorporation of metabolic chemical reporters on to live cells, cell harvesting techniques, and CuAAC click chemistry.…”
Section: Introductionmentioning
confidence: 99%